Are Parents More Likely to Be Unemployed? A Study of Nine Western Democracies - Richard Stjärnfäldt (Luxembourg Income Study (LIS), 2016)
The relation between parenthood and market work is an established field of study in demography. This thesis specifically focuses on the relation between parenthood and unemployment, the involuntary absence of work, in a cross sectional study of nine western democracies. The studied countries are Canada, France, Germany, Italy, Poland, Spain, Sweden, the United Kingdom, and the United States. A significant relation between motherhood and unemployment where found in Germany, Poland, the United States, and to a lesser extent in the United Kingdom.
Keywords: 330; gender; unemployment; welfare regimes; employment; part time work; children; mothers; human capita